Who uses NHS health checks? Investigating the impact of ethnicity and gender and method of invitation on uptake of NHS health checks. Issue 1 (December 2016) - Cook, Erica; Sharp, Chloe; Randhawa, Gurch; Guppy, Andy; Gangotra, Raj; Cox, Jonathon
Abstract Background NHS Health Checks is a national risk assessment prevention programme for all individuals aged 40-74 that reside in England. Through the systematic assessment of an individual's ten year disease risk, this programme aims to provide early identification and subsequent management of this risk. However, there is limited evidence on how socio-demographic factors impact on uptake and what influence the invitation method has on uptake to this programme. Methods NHS Health Check data from April 2013 to March 2014 was analysed (N  = 50, 485) for all 30 GP Practices in Luton, a culturally diverse town in England, UK. Data was collected for age, ethnicity, uptake (attendance and non attendance) and invitation method (letter written, verbal face-to-face, telephone). Actual usage of NHS Health Checks was determined for each ethnic group of the population and compared using Chi-square analysis. Results The overall uptake rate for Luton was 44 %, markedly lower that the set target of 50–75 %. The findings revealed a variation of uptake in relation to age, gender, level of deprivation. Ethnicity and gender variations were also found, with 'White British' 'Black Caribbean' and 'Indian' patients most likely to take up a NHS Health Check. However, patients from 'Any Other White Background' and 'Black African' were significantly less likely to uptake an NHS Health Check compared to all other ethnic groups. Ethnicity and gender differences were also noted in relation to invitation method. Conclusions The findings revealed that different invitation methods were effective for different ethnic and gender groups. Therefore, it is suggested that established protocols of invitation are specifically designed for maximizing the response rate for each population group. Future research should now focus on uncovering the barriers to uptake in particular culturally diverse population groups to determine how public health teams can better engage with these communities.